A Functional Perspective on Gender Associated Patterns in Kurdish EFL University Students’ Conversational Performance - ABDULRAHMAN, Barham Sattar (The Eurasia Proceedings of Educational and Social Sciences, 2018)
The current study focuses on gender associated communication styles that male and female Kurdish EFL senior university students have while using English face-to-face in academic contexts. It hypothesizes that both male and female EFL students have their own style of language with some similarities and differences. The differences might be due to male/female misunderstanding of each other while having face-to-face interaction. Moreover, the differences could not be noticed in academic communication of all Kurdish EFL university students unless the situational influences of each style are evaluated. The study concludes that social and cultural variations affect the language style used by Kurdish EFL university students. This study could be helpful for the university lecturers to have a better understanding of how the process of learning should be enhanced and made more effective and successful.